2006
DOI: 10.1007/s00586-006-0256-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty at C2: case report of a patient with multiple myeloma and a literature review

Abstract: Percutaneous vertebroplasty (PVP) of the axis is a challenging procedure which may be performed by a percutaneous or a transoral approach. There are few reports of PVP at the C2 level. We report a case of unstable C2 fracture treated with the percutaneous approach. The fracture was the first manifestation of multiple myeloma in a previously healthy 47-year-old woman. After local radiotherapy and chemotherapy, the fracture was still unstable and the patient had been continuously wearing a stiff cervical collar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 13 publications
(17 reference statements)
1
24
0
1
Order By: Relevance
“…Several small studies and case series have demonstrated a beneficial effect, 1,2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] but the largest sample size is composed of only 18 patients. Many barriers prevent the accumulation of a large patient cohort in the myeloma population, and these include reduced survival time of myeloma patients, the relative rarity of vertebroplasty treatment in myelomatous fractures, and a higher threshold of treatment criteria for patients with diffuse disease.…”
mentioning
confidence: 99%
“…Several small studies and case series have demonstrated a beneficial effect, 1,2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] but the largest sample size is composed of only 18 patients. Many barriers prevent the accumulation of a large patient cohort in the myeloma population, and these include reduced survival time of myeloma patients, the relative rarity of vertebroplasty treatment in myelomatous fractures, and a higher threshold of treatment criteria for patients with diffuse disease.…”
mentioning
confidence: 99%
“…Furthermore, the axis is a crucial part of a complex biomechanical system which participates in flexion, extension, rotation, lateral bending, and axial loading as well as distraction. 14,20,25 Hence, arthrodesis or fixation may not be clinically acceptable due to restricted range of motion. Percutaneous vertebroplasty allows the option of preserving the mobility of the upper cervical spine, although surgical stabilization is required if vertebroplasty fails to provide sufficient stability.…”
Section: Discussionmentioning
confidence: 99%
“…As in patients with aneurysmal bone cysts, hemangiomas, myelomas, and fibrous dysplasias, transoral vertebroplasty has been reported to alleviate cervical pain in patients with osteoporotic fractures and osteolytic metastases in a rapid and durable manner. 5,6,10,[25][26][27] The anterolateral approach for upper cervical spine vertebroplasty has gained popularity because it can be performed without general anesthesia or endotracheal intubation. The anterolateral route entails less risk of infection as the needle does not traverse the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] We employed a postero-lateral approach, although novel approaches including anterior and even trans-oral access of the cervical spine have been reported.…”
mentioning
confidence: 99%